The type of religiosity as a factor influencing the acceptance or rejection of scientific theories: the case of evolution. - Athanasiou, Kyriacos; Efstratios, Katakos; Papadopoulou, Penelope; Stanissavljevic, Jelena (DOI: 10.13140/2.1.4170.7521, 2012)
Our present contribution is a resume of a series of our studies by which we make an effort to explore the factors that are related to the acceptance of evolutionary theory among Greek and other variouscountries perspective and active educators using the conceptual ecology for biological evolution as a theoretical lens. Our central question refers to the role of the type of religiosity of a certain population in making their willingness for acceptance or rejection of evolution in the school environment. The Theory of Evolution (ET) is considered as concept - threshold that needs to be passed before someone can develop his/her understanding (Kinchin 2010) of a broader perspective of natural phenomena and of the nature of science. Most educational research has shown that the result of the teaching of ET is not positive in different parts of the world. Moreover research shows that the acceptance of the ET is restricted and the knowledge is limited and controversial among school science students and teachers. Large percentages of science teachers—close to a majority in many samples—reject ET and support the teaching of antievolutionary ideas in schools (Nehm & Schonfeld, 2007). Thus evolution remains a problematic subject for many science teachers. We make the hypothesis that the type of qualitative characteristics of the religion a nation or population group holds, is an essential factor in determining the level of acceptance of evolution, and their readiness to make changes in their believes, as well. More specifically, we advocate that the student and teacher populations that come from countries with a Greek-Orthodox background are m​